MENGEMBANGKAN KETERAMPILAN MOTORIK HALUS ANAK MELALUI MERONCE DI SEOLAH DASAR - Ade Islamiati; Farida Mayar; Desyandri (STKIP Subang, 2023)
This type of research is classroom action research where the goal to be achieved in this research is to develop students' fine motor development through teaching activities and demonstration activities. This action research the writer did through 2 cycles. The subjects that the authors used in this study were class Va students at SD Negeri 07 Koto Alam, Kecamatan Pelambayan Kabupaten Agam. The method used in this study is a descriptive statistical analysis method and also a quantitative method. From this study the results of the data obtained in cycle I found data of 22.43%. While in cycle II there was an increase to 82.01%. From these data it was concluded that meronce activities were able to improve the motor development of students at SD Negeri 07 Koto Alam, Kecamatan Pelambayan Kabupaten Agam regency